An assessment of heavy metal exposure risk associated with consumption of cabbage and carrot grown in a tropical Savannah region. Issue 1 (1st January 2021) - Fonge, Beatrice Ambo; Larissa, Makeu Tangoufo; Egbe, Awo Miranda; Afanga, Yannick Afanga; Fru, Nsoh Goodenough; Ngole-Jeme, Veronica Mpode
ABSTRACT: Indiscriminate use of fertilizers by vegetable growers and poor water quality of irrigational water characterize vegetable production in most parts of Cameroon. The concentrations of As, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn in the soil, cabbage and carrot cultivated in Santa, North West Region, Cameroon were assessed to determine potential ecological and human health risk associated with the consumption of these two vegetables. Heavy metal concentrations were determined using a ContrAA 300 Atomic Absorption Spectrophotometer after microwave digestion. The concentrations of As (0.51 mg/kg and 0.38 mg/kg), Co (1.41 mg/kg and 1.39 mg/kg) and Pb (1.36 mg/kg and 1.31 mg/kg) in the cabbage and carrot, respectively, were above the WHO/FAO, permissible limits for human consumption. Health risk index values for Co in cabbage (2.31 mg/kg) and carrot (2.26 mg/kg) indicated significant risks from Co exposure. Geo-accumulation Index indicated that soils from most sites were contaminated. The populations consuming these vegetables are at risk of As, Co and Pb toxicity. Monitoring and sensitization of farmers on the effects of indiscriminate use of agrochemicals is very necessary to protect the health of consumers and preserve the soil quality.